In order to subtract two like fractions, we may follow the following steps:

Step 1) Obtain the two fractions and their numerators.

Step 2) Subtract the smaller numerator from the bigger numerator.

Step 3) Retain the common denominator of all fractions.

Step 4) Write the fraction as \(\frac{Result in Step (2)}{Result in Step (3)}\)

Subtracting Fractions When the Denominators are the Same Example 1:

Subtract \(\frac{3}{10}\) from \(\frac{8}{10}\).

Solution: We have to find

= \(\frac{5}{10} = \frac{5 \div 5}{10 \div 5}\) { Dividing numerator and denominator by their HCF }

= \(\frac{1}{2}\).

Subtracting Fractions When the Denominators are the Same Example 2:

Compute \(\frac{5}{12} – \frac{7}{12} + \frac{11}{12}\)

Solution: We have, \(\frac{5}{12} – \frac{7}{12} + \frac{11}{12}\)

= \(\frac{5 – 7 + 11}{12} = \frac{11 – 2}{12}\)

= \(\frac{9}{12} = \frac{9 \div 3}{12 \div 3}\) { Dividing numerator and denominator by their HCF }

= \(\frac{3}{4}\).

Subtracting Fractions When the Denominators are the Same Example 3:

Simplify \(4\frac{2}{3} + \frac{1}{3} – 4\frac{1}{3}\).

Solution: We have, \(4\frac{2}{3} + \frac{1}{3} – 4\frac{1}{3}\)

= \(\frac{4 X 3 + 2}{3} + \frac{1}{3} – \frac{4 X 3 + 1}{3}\)

= \(\frac{14}{3} + \frac{1}{3} – \frac{13}{3}\)

= \(\frac{14 + 1}{3} – \frac{13}{3} = \frac{15}{3} – \frac{13}{3}\)

= \(\frac{15 – 13}{3} = \frac{2}{3}\).